ETOS KERJA SEKOLAH TINGGI EKONOMI DAN BISNIS SYARIAH (STEBIS) INDO GLOBAL MANDIRI - Fachrurrozi Fachrurrozi; Fadilla Fadilla (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2021)
In 2014 the College of Sharia Economics and Business was inaugurated with the aim of fulfilling the wishes of the people of South Sumatra in general regarding the procedures for the sharia economy. This research tries to study how the work ethic in STEBIS IGM. From the results of research observations, it was found that in principle, the work ethic at STEBIS IGM was very good. This can be seen from the attitude of employees from STEBIS who are disciplined, have integrity and desire to move forward, trying to put everything in line with their respective functions and duties. In addition, the foundation also fully supports by providing rewards and punishments that are in accordance with the employees' work.